What Is Neural Plasticity? - Eugenin-Leon, J (Springer New York LLC, 2017)
“Neural plasticity” refers to the capacity of the nervous system to modify itself, functionally and structurally, in response to experience and injury. As the various chapters in this volume show, plasticity is a key component of neural development and normal functioning of the nervous system, as well as a response to the changing environment, aging, or pathological insult. This chapter discusses how plasticity is necessary not only for neural networks to acquire new functional properties, but also for them to remain robust and stable. The article also reviews the seminal proposals developed over the years that have driven experiments and strongly influenced concepts of neural plasticity. © Springer International Publishing AG 2017.
Keywords: Neuronal plasticity; Homeostatic plasticity; Hebbian plasticity